Budi Wasito, Rancang Bangun Sistem Informasi Koperasi Karyawan iBii berbasis Web - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
Along with the increased of human interest in finding a new breakthrough, internet world has grown enormously. Such long range information system has been used and adopted by many organizations with many goals and purpopes. Such enormous growth has also been used by educational organizations, by applying internet as helping tools in learning process and organization management process.Â  This research uses interviews and observations on IBII Campus. Human resource application was developed with PHP web programming language and MySQL database application along with android programming language as additional application. The result of this research is web and mobile based cooperative information system. This application aims to assist the organization in managing its members, loans and savings data from each members. The conclusion of this research is the application of cooperative information system provides convenience in conducting the process of managing cooperativeâ€™s activities.